In vitro and in vivo study of commercial calcium phosphate cement HydroSet™. Issue 1 (7th November 2016) - Kent, Niall W.; Blunn, Gordon; Karpukhina, Natalia; Davis, Graham; de Godoy, Roberta Ferro; Wilson, Rory M.; Coathup, Melanie; Onwordi, Lyris; Quak, Wen Yu; Hill, Robert
Abstract: The commercial calcium phosphate cement, HydroSet™, was investigated in vitro, studying phase formation, compressive strength and setting time, followed by an ovine in vivo study to measure osseointegration, bone apposition and bone‐to‐graft contact. The X‐ray diffraction and 31 P Magic Angle Spinning Nuclear Magnetic Resonance (MAS NMR) results showed the initial formation of octacalcium phosphate and hydroxyapatite at one hour. Over 7 days the octacalcium phosphate transformed to apatite, which was the only crystalline phase of the cement at 28 days. This apatite phase is thought to be a calcium deficient apatite. In the scanning electron microscopy, histological images of 12‐week ovine in vivo results showed a high degree of osseointegration, 92.5%. Compressive strength comparisons between in vitro and in vivo measurements showed a dramatic difference between the in vitro measurements (highest 25.4 MPa) and in vivo (95 MPa), attributed to bone ingrowth into the cement in vivo . To the best of our knowledge this is the first time phase evolution of HydroSet™ and the properties studied in vitro complement the in vivo evaluation of the cement in a publication. The significance of the new finding of initial formation of octacalcium phosphate in this cement is discussed. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 21–30, 2018.